Building supplier innovation triads: The effects of leadership relationships and alliance partner diversity. Issue 2 (8th January 2020) - Potter, Antony; Paulraj, Antony
Abstract : Purpose: The past decade has seen substantial changes in how organizational leaders work with external stakeholders to improve innovation performance. As leaders have encouraged the extensive involvement of suppliers and customers into the innovation process this has led to the formation of supplier innovation triads that are often governed by a portfolio of strategic alliances. The purpose of this paper is to explore how leaders' inter-firm relationships and strategic alliances influence the development of supplier innovation triads. Design/methodology/approach: The sample of firms in the Toyota supplier association is constructed from multiple data sets, including the Japan Patent Office, BoardEx and S&PCapitalIQ. The authors test the hypotheses using multivariate techniques, moderation analysis and endogeneity tests. Findings: The results indicate that leadership relationships to Toyota and its suppliers have a positive effect on the formation of supplier innovation triads. The authors find that firm–external leadership relationships and alliance partner diversity have differential moderating effects on how customer and supplier leadership relationships could be used to build supplier innovation triads. Research limitations/implications: The results focus on the firms within the Toyota supplier association, and this limits the paper's generalizability. Although patent data provide a detailed information resource, it do not capture all collaborations. Originality/value: The authors expand the leadership literature by undertaking one of the first studies of inter-firm leadership relationships and their differential effects on innovation triads. The authors contribute to the literature by exploring the antecedents and moderating factors that influence buyer–supplier–supplier triads within an innovation setting.